Small-sided games in female soccer players: a systematic review - De Dios-Álvarez, V.; Lorenzo-Martínez, M.; Padrón-Cabo, A.; Rey, E. (The Journal of Sports Medicine and Physical Fitness, 2022)
INTRODUCTION: This systematic review aimed to analyze the literature on small-sided games (SSGs) from a physiological and physical perspective in female soccer players. EVIDENCE ACQUISITION: A systematic review of Web of Science, PubMed, Scopus and SPORTDiscus was performed according to PRISMA (Preferred, Reporting Items for Systematic reviews and Meta-Analysis) Guidelines. Studies informed about physical and/or, physiological-responses during SSGs played by young and/or adult amateur and/or professional female soccer players were included. Information regarding study information, population, intervention data, instruments, variables analyzed, and outcomes were elucidated. EVIDENCE SYNTHESIS: The search returned 2944 records. After screening against set criteria, a total of 13 manuscripts were fully reviewed. The present review grouped studies according to the three following age categories taking sample`s mean age into account: Under-19 as young players and senior female players (>19 years old). The most common topics of analysis were: 1) player number; 2) pitch area and game surface; 3) sex differences; and 4) training regimens. CONCLUSIONS: This review provides useful information on the complex relationship between technical, physical and physiological interactions in SSGs and how manipulating these types of variables can improve the soccer training process.